Pirates, the rebel generation: Rock music as a space of political dissidence in Nicaragua at the turn of 20th century - Barinova, Martina (2023)
This investigation traces the history of rock music in Nicaragua since the roots, that is 1930’s when the notion of Nicaraguan national culture is built. The role of music in different critical moments of recent Nicaraguan history is explored with respect to the importance of radio in spreading and popularizing determined music genres and political messages. Based on personal interviews and analysis of video-documents we describe the political tendencies within the community around alternative and rock music after the year 1990. The nineties show to be a decade of generational rupture when rock becomes an anti-system movement and a platform of alternative culture and expression of political dissidence, which, at the same time, shows continuity with the political thinking of the previous generation.